Nonreversal of adrenal hypofunction after treatment of adrenal tuberculosis - Bashir Ahmad Laway; Shahnaz Ahmad Mir; Mohd Ashraf Ganie; Feroze Shaheen; Parvaiz Ahmad Shah (SpringerOpen, 2015)
Tuberculosis of the adrenal glands is a common cause for Addison's disease in developing countries. Whether treatment of tuberculosis normalizes adrenocortical function in these patients is controversial. We are reporting two cases of Addison's disease because of adrenal tuberculosis, in whom treatment with antitubercular drugs did not restore normal adrenal functions. We conclude that treatment of tubercular Addison's disease does not lead to normalization of adrenocortical function.